ANTIFUNGAL ACTIVITY OF PANCHAWALKALA KWATHA AND PANCHAWALKALA SHATADAUTA GHRITA (International Journal of Ayurveda and Pharma Research, 2021)
Panchawalkala is one of the ideal herbal combinations in Ayurveda and it has therapeutic properties such as Vranaropana, Shothahara, Graahi and Visarpahara. And also researchers have been proven anthelmintic, antimicrobial, wound healing and anti-inflammatory activities of these plants in combination and individual too. Ghrita (Ghee) is one of the oil preparation made by cow’s milk and it has Balavardhaka, Ojovardhaka, Vayasthapaka, Dhatuposhaka properties and is supreme in Snehana Dravyas. Panchawalkala is widely used in Kwatha and Powder form. Shatadauta Ghrita is the most famous form of the Ghee. The advantages of different innovative preparations are; increased shelf life, ready to use, better acceptability and ease of application. This study was planned to evaluate in-vitro antifungal activity of traditional Panchawalkala Kwatha and innovative Panchawalkala Shatadauta Ghrita (the Ghrita, hundreds times purified by Panchawalkala Kwatha). It was assessed by adopting agar diffusion method. Each agar plate was divided into four equal parts and was cultivated the Candida albicans. Replicator device was used to inoculate multiple specimens on to two parts of three series of plates with respective drugs. Further, responses of organism to the trial drugs were measured and compared with standard drug of Fluconazole (+ve control) and distilled water (-ve control) by using other two parts of the agar plates. All the plates were incubated at 37°C for 24 hours. According to the findings, Panchawalkala Shatadauta Ghrita has an antifungal effect than Panchawalkala Kwatha. Fluconazole is the best antifungal drug among these and distilled water does not have any antifungal action. Hence, it can be concluded that, Panchawalkala Shatadauta Ghrita has antifungal activity rather than Panchawalkala Kwatha but not effective than Fluconazole.